Rancangan Pemetaan Sebaran Covid-19 di Kota Padang Berbasis Web Geospasial - Yuhefizar; Ervan Asri; Nasrullah (Ikatan Ahli Informatika Indonesia, 2020)
Starting from Wuhan in China, the new type of corona virus (SARS-CoV-2) has spread to various countries in the world, including Indonesia, which is known as the COVID-19 disease. On March 11, 2020, WHO declared COVID-19 a pandemic, which is an epidemic that has spread to several countries or continents, and generally affects many people. The President of the Republic of Indonesia has issued Presidential Decree No. 12/2020 concerning the determination of COVID 19 as a non-natural national disaster. This indicates that the Covid 19 Pandemic is increasingly widespread in Indonesia, including the city of Padang and that strategic steps are needed to fight its spread, one of which is in providing information that is easy to read and understand by the public. For this reason, in this study we utilize geospatial web technology to disseminate Covid 19 information to urban villages in Padang City. Geospatial Web is part of WebGis which is able to provide location-based information in more detail and in map form and is presented using web technology so that it can be accessed by the wider community easily. There are five types of geospatial web services used, namely Web Map Service, Web Feature Service, Web Coverage Service, Web Map Tile Service, and Web Processing Service. It is hoped that the results of this study can contribute to the Padang city government and its community regarding the information on the spread of Covid-19 in more detail and location-based.